Does the company's economic performance affect access to occupational health services? - Suhonen Aki; Kankaanpää Eila; Valtonen Hannu (BMC, 2009)
Abstract Background In Finland like in many other countries, employers are legally obliged to organize occupational health services (OHS) for their employees. Because employers bear the costs of OHS it could be that in spite of the legal requirement OHS expenditure is more determined by economic performance of the company than by law. Therefore, we explored whether economic performance was associated with the companies' expenditure on occupational health services. Methods We used a prospective design to predict expenditure on OHS in 2001 by a company's economic performance in 1999. Data were provided by Statistics Finland and expressed by key indicators for profitability, solidity and liquidity and by the Social Insurance Institution as employers' reimbursement applications for OHS costs. The data could be linked at the company level. Regression analysis was used to study associations adjusted for various confounders. Results Nineteen percent of the companies (N = 6 155) did not apply for reimbursement of OHS costs in 2001. The profitability of the company represented by operating margin in 1999 and adjusted for type of industry was not significantly related to the company's probability to apply for reimbursement of the costs in 2001 (OR = 1.00, 95%CI: 0.99 to 1.01). Profitability measured as operating profit in 1999 and adjusted for type of industry was not significantly related to costs for curative medical services (Beta -0.001, 95%CI: -0.00 to 0.11) nor to OHS cost of prevention in 2001 (Beta -0.001, 95%CI: -0.00 to 0.00). Conclusion We did not find a relation between the company's economic performance and expenditure on OHS in Finland. We suppose that this is due to legislation obliging employers to provide OHS and the reimbursement system both being strong incentives for employers.